2018
DOI: 10.1080/08897077.2017.1365804
|View full text |Cite
|
Sign up to set email alerts
|

The Willingness of People who Inject Drugs in Boston to use a Supervised Injection Facility

Abstract: Most respondents (91.4%) reported willingness to use a SIF. Respondents with substance use behavior reflecting high risk for overdose were significantly more likely to be willing to use a SIF. Respondents with behaviors that contribute to public health burden of injection drug use were also significantly more likely to be willing to use a SIF. Results indicate that this intervention would be well utilized by individuals who could most benefit from the model. As part of a broader public health approach, SIFs sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Their representations are consistent with the objectives of this structure, which means that they understand well the potential benefit of a DCR. This is in accordance with several other studies conducted in different countries were DCR operate [ 25 30 ]. The only exception is their disbelief in its social objective efficacy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Their representations are consistent with the objectives of this structure, which means that they understand well the potential benefit of a DCR. This is in accordance with several other studies conducted in different countries were DCR operate [ 25 30 ]. The only exception is their disbelief in its social objective efficacy.…”
Section: Discussionsupporting
confidence: 93%
“…In the international literature, the opinion of PWUD regarding DCR has been extensively investigated in several countries: surveys and qualitative studies have shown that they were predominantly in favor of DCRs in Canada, Australia, Denmark, UK, and in the USA [ 25 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…These data demonstrate high willingness to use SCS among PWUD indicating their potential for engaging PWUD and intervening on their risk environment to help avert the most extreme consequences of the opioid epidemic. While SCS are not legally sanctioned in the USA, a number of cities are advocating for their implementation [14,27]. Our study adds to the nascent USbased literature and could be useful in informing future efforts around SCS implementation.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have examined willingness to use SIFs among people who inject drugs (PWID) in the USA; three quantitative studies showed high willingness among PWID in San Francisco (85%), Boston (91%), and Rhode Island (87%) [12][13][14]. In all of these studies, elevated willingness to use a SIF was observed in high-risk subgroups such as PWID engaging in public injection and speedball use (concomitant heroin and cocaine use) and individuals with complex morbidities and high health service needs.…”
mentioning
confidence: 99%
“…Our review was limited to looking at country-level data, when we know that there can be substantial variation within a country. For example, in the USA, there were eligible studies with estimates of recent non-fatal overdose ranging from 9% in San Francisco to over 50% in Boston (Leon, Cardoso, Mackin, Bock, & Gaeta, 2018;Robinson et al, 2017). Similarly, pooling studies in Viet Nam reporting on lifetime non-fatal overdose resulted in a lower estimate than recent non-fatal overdose in our results.…”
Section: Discussionmentioning
confidence: 99%